PHYTOCHEMICAL STUDIES AND ANTIMICROBIAL COMPOUNDS FROM FRUIT OF THESPESIA POPULNEA - NANDHINI S, USHA; V, Radhika; S, Manisha; V, Anusha Jeslin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To study the phytochemical analysis and antimicrobial compounds from fruits of Thespesia populnea. Methods: The determination of antimicrobial activity of fruit extract was done by agar well diffusion method. Active compounds were extracted by different solvent extraction methods. The presence of active compounds was confirmed by ultraviolet-visible spectrophotometry, Fourier transform infrared spectroscopy and gas chromatography-mass spectrometry analysis (GC-MS). Results: The active extract was identified by the GC-MS analysis and it was revealed that the presence of oleic acid, pentadecanoic acid, and N-hexadecanoic acid. Conclusion: This method adopted and extracted purified active metabolites and can be fruitfully employed for obtaining novel antibiotic compoundsÂ to treat human pathogenic bacterial and fungal diseases. Keywords: Thespesia populnea (L.), Gas chromatography-mass spectrometry, Fourier transform infrared spectroscopy, Antimicrobial, Phytochemical.